Caracterização hidrológica e hidrossedimentológica em bacia hidrográfica com finalidades experimentais - Valentino, César Henrique (2019)
The objective of this work was to make the Chapadao Basin an Experimental Hydrographic Basin for the development of studies related to water and environmental studies. In a specific way, the characterization of the rain-runoff relation was carried out and the relationship of the erosivity of the rains with the production of sediments was analyzed. It was carried out the physiographic characterization of the basin and its instrumentation, with the installation of a fluviometric station in the control section. From December 2017 to October 2018, flow velocity and water level data were collected for the construction of the key curve of the monitoring section, as well as the Suspended Solids Concentration (CSS) data, which allowed the elaboration of a sediment discharge curve to determine the total mass of suspended solids carried in erosive events of the studied period. For some classified erosive events, the runoff coefficient values by an analogy to the Lloyd-Davies method were verified and the SCS Curve Number Method was applied. The values found for the runoff coefficient were in the range of 0.01 to 0.57 and its behavior could be directly related to precipitation of the event and soil moisture conditions. The Curve Number Method indicated that the soil in the region has a high infiltration potential, CN and potential infiltration values, for the Antecedent Moisture Conditions AMC I, AMC II and AMC III were respectively, 22.23 and 888.6mm; 44.60 and 315.5mm, 60.18 and 168.1mm. The comparison of the methods of obtaining the superficial flow showed that the Hydrograph Method is the most indicated for the studied area. The relationship between the MSST and the rainfall erosivity analyzed returned an interesting value of the soil erodibility in the region, although more studies are necessary in regard to this matter.